PELATIHAN PEMBUATAN KOHORT SISWA UNTUK MENCARI EFISIENSI PENYELENGGARAAN PENDIDIKAN DI DESA BOBOJONG KABUPATEN CIANJUR - Matin Matin; Masduki Ahmad; Elsah Fanisyah (Universitas Majalengka, 2022)
Abstract This activity aims to train teachers of Bobojong Village Elementary School, Cianjur Regency to have: 1). Understanding of the concept of student cohort needed in educational planning to realize an effective school. 2) The ability to process educational data into student cohorts to find the level of efficiency that can help facilitate the realization of effective schools. 3) Ability to analyze student cohorts needed in realizing an effective school. The activity methods used are brainstorming methods, interactive discussions, seminars, individual assignments, and performance evaluation. The results of this training activity are that the teachers of Bobojong Village Elementary School, Cianjur Regency as training participants have: 1) had an understanding of the concepts of data and information needed in educational planning to produce effective school management; 2) able to compile a cohort of students that can be used to find various educational problems in order to facilitate the process of effective school management; 3) able to find the efficiency of education delivery from the student cohort compiled and follow up by finding solutions to improve the efficiency of the implementation of school education for which they are responsible; and 4) be able to identify population data processing techniques and educational data that are often used for educational planning purposes. To see the more tangible impact of this training activity, this training needs to be followed up by providing assistance to school teachers in need, and partnering with the KKG or with the local Religious Education Office. It should be considered to form a foster school for Jakarta State University as a form of the third dharma of the Tri Dharma of Higher Education, namely the dharma of community service. Abstrak Kegiatan ini bertujuan untuk melatih guru Sekolah Dasar Desa Bobojong Kabupaten Cianjur agar memiliki: 1). Pemahaman terhadap konsep kohort siswa yang diperlukan dalam perencanaan pendidikan guna mewujudkan sekolah efektif. 2) Kemampuan mengolah data pendidikan kedalam kohort siswa guna menemukan tingkat efisiensinya yang dapat membantu memperlancar perwujudan sekolah efektif. 3) Kemampuan menganalisis kohort siswa yang dibutuhkan dalam mewujudkan sekolah efektif. Metode kegiatan yang digunakan ialah metode curah pendapat (brainstorming), diskusi interaktif, seminar, tugas individual, dan evaluasi kinerja. Hasil kegiatan pelatihan ini adalah para guru Sekolah Dasar Desa Bobojong Kabupaten Cianjur sebagai peserta pelatihan telah: 1) memiliki pemahaman terhadap konsep data dan informasi yang diperlukan dalam perencanaan pendidikan guna menghasilkan manajemen sekolah efektif; 2) mampu menyusun kohort siswa yang dapat digunakan untuk menemukan berbagai permasalahan pendidikan guna memperlancar proses pengelolaan sekolah efektif ; 3) mampu menemukan efisiensi penyelenggaraan pendidikan dari kohort siswa yang disusun dan menindaklanjutinya dengan mencari solusi untuk meningkatkan efisiensi penyelenggaraan pendidikan sekolah yang menjadi tanggungjawabnya; dan 4) mampu mengidentifikasi teknik pengolahan data penduduk dan data pendidikan yang kerap digunakan untuk keperluan perencanaan pendidikan. Untuk melihat dampak yang lebih nyata dari kegiatan pelatihan ini maka pelatihan ini perlu ditindaklanjuti dengan memberikan pendampingan kepada para guru sekolah yang membutuhkan, dan bermitra dengan KKG atau dengan Dinas Pendidikan Agama setempat. Perlu dipertimbangkan untuk membentuk sekolah binaan bagi Universitas Negeri Jakarta sebagai wujud dharma ketiga dari Tri Dharma PerguruanTinggi yaitu dharma pengabdian kepada masyarakat.